Combating Coloniality: the cultural policy of post-colonialism - Mulcahy, Kevin V. (Políticas Culturais em Revista, 2019)
The distinguishing characteristic of cultural policy in countries characterized by a legacy of coloniality is the importance of the identity formation and the politics that are involved in formulating its definition. At root, coloniality is an experience involving dominating influence by a stronger power over a subject state. However, this is not just a matter of external governance or economic dependency, but of a cultural dominance that creates an asymmetrical relationship between the ‘center’ and the ‘periphery,’ between the ruling ‘hegemon’ and the marginalized ‘other.’ In these circumstances, what constitutes an “authentic” culture, and how this informs national identity, is a central political and social concern.